The Asset Recovery Strategy: Illicit Enrichment, Money Laundering and Confiscation, Some Brushstrokes on Ecuadorian and Spanish Legislation - Vélez-Zhindón, María Teresa (DICERE Revista de Derecho y Estudios Internacionales, 2024)
“Modern criminal law” gives rise to a certain “disharmonization of criminal law”, which leads to the creation of “new criminal offenses”, typification techniques close to sanctioning models of administrative law, as in the case of the crime of illicit enrichment in the form of disobedience (as the Spanish legislator intends to call it), the denaturalisation of accessory consequences, such as extended confiscation (Spanish legislation), as well as in the classification of crimes that punish post-criminal conduct, such as the crime of illicit enrichment and the crime of money laundering. In this, both the Ecuadorian and Spanish legislators seek procedural shortcuts for those crimes where the criminal origin of the increase in wealth cannot be determined, an ‘inexplicable’ or ‘unjustified’ origin of wealth, which is presumed to be the result of a previous crime. This leads us to consider whether ‘modern criminal law’, specifically in the recovery of assets of illicit origin, can result in a conviction and/or in confiscation of assets on the basis of presumptions of guilt or presumptions of the illicit origin of assets.